Ketahanan Bahasa Indonesia Di Era Milenial - Syamsudin, Oom Rohman (UI Scholars Hub, 2018)
This brief study aims at discussing the current condition of the Indonesian language which is sadly demonstrating signs of “deterioration”, as one of the consequences of the present social media assault. Ever more progress in the advances of sophisticated science and technology has broken down the endurance of standard Indonesian as demonstrated particularly by the millennial generation. This code mixing in language use is generally noticeable in writing a mixture of Indonesian and English, a common practice among today’s young generation in Twitter, Instagram and other social media. The use of elements of both language simultaniously, however, does not violate linguistic rules of either language. Nevertheless, it should be borne in mind that language is a constantly changing device, at the same time it represents the symbol of a country, signifying love, pride, respect, and above all: a national identity of a country. These are features that should be instilled in the minds of the younger generation, in order to ensure the preservation of the Indonesian language.